Authoritarianism and marketisation in higher education:implications of China’s rise for cosmopolitan academic citizenship - Burnay, Matthieu; Pils, Eva (International journal of human rights, 2022)
Academic citizenship has long been recognised as a core aspect of belonging to institutions of scholarship and teaching. According to the normative conception adopted here, academic citizenship encompasses engagement with and service to society. It is an inherently cosmopolitan and liberal-democratic idea, because its point is the promotion of the free exchange of academic ideas in the service of society, regardless of national borders. Yet, while a cosmopolitan conception of academic citizenship is broadly speaking compatible with the laws and politics of liberal democracies bound to safeguard academic freedom, it is in tension with authoritarian political-legal orders, such as that of the People’s Republic of China, which has in certain contexts transformed citizenship into an instrument of repression and population control. The paper is divided into three parts. We begin by developing a cosmopolitan conception of academic citizenship that allows us to analyse and assess the connection between membership of the academic community and academic freedom. We juxtapose the cosmopolitan conception of academic citizenship with marketised and authoritarian conceptions of academic citizenship (1). We then discuss the ways in which the Chinese government’s authoritarian advance impacts academic freedom abroad, arguing that a prevalent, reductionist, marketised conception of academic citizenship renders academic institutions particularly vulnerable (2). Finally, we critically assess state and non-state actor responses to these challenges (3). We argue that a cosmopolitan understanding of academic citizenship requires a fundamental rethinking of the existing mechanisms and initiatives to protect and promote academic freedom in China and beyond.
CRIS-Team Scopus Importer:2023-03-21
Keywords: academic citizenship; academic freedom; China; internationalisation; marketisation